2023
DOI: 10.1051/0004-6361/202346001
|View full text |Cite
|
Sign up to set email alerts
|

Bubbles and outflows: The novel JWST/NIRSpec view of the z = 1.59 obscured quasar XID2028

Abstract: Quasar feedback in the form of powerful outflows is invoked as a key mechanism to quench star formation in galaxies, although direct observational evidence is still scarce and debated. Here we present Early Release Science JWST NIRSpec IFU observations of the z = 1.59 prototypical obscured Active Galactic Nucleus (AGN) XID2028: This target represents a unique test case for studying quasar feedback at the peak epoch of AGN-galaxy co-evolution because extensive multi-wavelength coverage is available and a massiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 88 publications
1
4
0
Order By: Relevance
“…Under this simple assumption, the dynamical timescale of the outflowing gas ranges from 0.1 Myr nearest the quasar to 10 Myr at 17 kpc from the quasar. In an independent analysis of the exact same Q3D NIRSpec data cube on XID 2028, Cresci et al (2023) recently reported [O III]-based outflow mass rate and energetics that agree within the errors (factor of ∼3) with the values reported here.…”
Section: Energetics Of the [O Iii] Outflowsupporting
confidence: 84%
“…Under this simple assumption, the dynamical timescale of the outflowing gas ranges from 0.1 Myr nearest the quasar to 10 Myr at 17 kpc from the quasar. In an independent analysis of the exact same Q3D NIRSpec data cube on XID 2028, Cresci et al (2023) recently reported [O III]-based outflow mass rate and energetics that agree within the errors (factor of ∼3) with the values reported here.…”
Section: Energetics Of the [O Iii] Outflowsupporting
confidence: 84%
“…The scale of the violent outflow in quasi-stellar objects (QSOs) ranges from a few parsecs (υ ∼ 0.1c) to ∼1 kpc (υ ∼ 10 2−3 km s −1 ) (e.g., Pounds et al 2003;Harrison et al 2016;Förster Schreiber et al 2019;Kakkad et al 2020). An outflow with an extension of 13 pc from the center of an SMBH has been identified for the ionized gas in the obscured AGN XID 2028 at z = 1.59 (Carniani et al 2016), which is recently confirmed by the Early Release Science JWST NIRSpec observations (e.g., Cresci et al 2023). Compared with the Very Large Array 3 GHz map, the authors argue that the extended outflow in the object is likely related to the lowluminosity radio jet.…”
Section: Introductionmentioning
confidence: 73%
“…However, the mass outflow rate of COSMOS-11142 is an order of magnitude larger than the typical values measured in local star-forming galaxies 23 , 24 . At high redshift, measurements of neutral outflows from Na i D absorption have been obtained for only a few quasars 25 , 26 , but observations of ultraviolet or submillimetre lines tracing neutral gas reveal high mass outflow rates in star-forming galaxies and AGN systems 11 .…”
Section: Mainmentioning
confidence: 99%